AB0272 Rheumatoid factor determines structural progression of rheumatoid arthritis also independently of disease activity. (23rd January 2014) - Aletaha, D.; Alasti, F.; Smolen, J.S.
Abstract : Background: The presence of rheumatoid factor (RF) is prototypic for rheumatoid arthritis (RA) and serves diagnostic and prognostic purposes. RF is associated with joint damage, but it is not clear if this is only due to its effects on disease activity or whether there are also independent effects. Objectives: We investigated whether the higher radiographic progression (change in total Sharp score, ΔTSS) seen in RF positive patients is dependent or independent of higher levels of disease activity, or both. Methods: We used methotrexate treatment arms from five different RA trials and compared ΔTSS in RF negative and RF high positive patients before and after matching for other prognostically important variables. The high positive positive group was selected to achieve a clear contrast in RF levels despite matching for other variables, and was defined as being above the median of all positives. We used Wilcoxon test for statistical comparison, and a number of sensitivity analyses to see if the results were robust. Results: Among 687 patients, 124 (18.1%) were RF negative, 562 (81.9%) RF positive, and 343 (50.0%) high positive (RF>160 U/ml). One year ΔTSS was 1.03±5.83, 3.23±8.10 and 3.58±8.18 (p<0.0001), respectively. Aside from RF, progression was associated with duration of RA, baseline damage, CRP and ESR. After matching for these variables, duration of RA, baseline disease activity indices, functional scores, and TSS were essentially identical in the matched 61 RF negative and 61 RF high positive patients. Nevertheless, the ΔTSS was significantly lower in the RF negative compared to their matched RF high positive counterparts (0.52±2.47 vs 3.09±8.28, respectively; p=0.029; table), and was seen particularly for erosions (0.31±1.88 vs. 2.07±5.62; p=0.035), but numerically also for joint space narrowing (0.21±1.26 vs. 1.02±3.31; p=0.162). Sensitivity analyses looking at the area under the curve of risk factors instead of baseline values only, as well as looking at the second year progression, supported the findings in the main analysis; no effect of RF on progression was seen in methotrexate plus TNF-inhibitor treated patients; the level of RF also appeared to be of relevance in an analysis of 29 matched triplets, which also included low positive patients (RF negatives: 0.19±2.47; low positive: 1.15±3.72; and high positive: 3.77±10.8; p=0.19 by Kruskal-Wallis test). Conclusions: Our data indicate that damage progression in seropositive RA patients is partly related to higher levels of disease activity, but partly also to independent effects of RF, particularly on bone damage. This identifies RF as an important independent risk factor for structural damage, and calls for an even more consequent pursuit of disease activity targets in seropositive RA patients. Disclosure of Interest: None Declared